Studies of the Transferrin Receptor on both Human Reticulocytes and Nucleated Human Cells in Culture: COMPARISON OF FACTORS REGULATING RECEPTOR DENSITY - Frazier, Janet L. (1982)
The transferrin receptor, present on reticulocytes and nucleated cells in tissue culture, has been measured with both immunoassay techniques and transferrin binding studies. The total cellular immunoreactive receptor is rapidly lost from erythrocytes during the process of reticulocyte maturation (from as many as 400,000 molecules to <20,000 molecules/reticulocyte). This event parallels the loss of cell surface transferrin binding sites and RNA content, and correlates with previous studies that have measured the decline in hemoglobin synthesis. Nonhemoglobin-producing normal human fibroblasts, which appear to have a much lower iron requirement than reticulocytes, contain similar numbers of immunoreactive receptors per cell (400,000 receptor molecules), when in an active state of proliferation. Although receptor density on fibroblasts is directly related to cell proliferation, our studies demonstrate that nonproliferating fibroblasts still retain significant numbers of immunoreactive receptors (150,000 molecules/cell) and transferrin binding sites. Since additional studies indicate that proliferating cells have increased iron uptake, a simple hypothesis would predict that the parallel increase in transferrin binding sites and total cellular immunoreactive receptor associated with proliferation is related to an increased cellular iron requirement. However, the number of immunoreactive receptor molecules and transferrin binding sites is not changed when cells are grown in iron-deficient media, or in media with added transferrin-iron. This result and the lack of marked differences in receptor number on both hemoglobin-producing and nonhemoglobin-producing cells indicate that other factors besides receptor density play major roles in the regulation of cellular iron uptake, retention, and loss.